Social responsibility of entrepreneurship IN THE FIELD OF CULTURE (Путеводитель предпринимателя, 2020)
The necessity of social responsibility of business in the field of culture giving it additional means for development is considered in the article, and also the possibility of enrichment of both parties as a result of these contacts is shown.